Research Note: A novel recombinant subgroup E isolate of the avian leukosis virus with a subgroup B-like Gp85 region in China - Li, Jing; Liu, Lanlan; Niu, Xinxin; Li, Jiukuan; Kang, Zhonghui; Han, Chunyan; Gao, Yulong; Qi, Xiaole; Wang, Yongqiang; Wang, Xiaomei; Zeng, Xiangwei (Poultry science, 2021)
The avian leukosis virus (ALV) strain DL00766 was isolated from a farm in China. The phylogenetic analysis showed that env had the highest homology with the E subgroup reference strain, ranging from 94.5% to 94.9%, whereas gp85 had the highest homology with the B and E subgroups, which were 89.0% to 91.3% and 91.3% to 91.8%. In addition, point mutation analysis of gp85 showed that a 400 bp long fragment in gp85 of DL00766 had the highest homology with subgroup B, ranging from 90.1% to 97.5%, and only 82.7% to 83.1% with E subgroup. These results indicate, DL00766 may be an AVL subgroup E isolate with a subgroup B-like gp85 region. This is also the first finding that the E subgroup is used as a recombinant subject, and the subgroup B provides a recombinant virus of an exogenous gene.